Manipulation of glycogen and sucrose synthesis increases photosynthetic productivity in cyanobacteria - Cantrell, Michael; Cano, Melissa; Sebesta, Jacob; Paddock, Troy; Xiong, Wei; Chou, Katherine J.; Yu, Jianping (Frontiers in Microbiology, 2023)
Photosynthetic productivity is limited by low energy conversion efficiency in naturally evolved photosynthetic organisms, via multiple mechanisms that are not fully understood. Here we show evidence that extends recent findings that cyanobacteria use “futile” cycles in the synthesis and degradation of carbon compounds to dissipate ATP. Disruption of the glycogen cycle or the sucrose cycle in the model cyanobacterium Synechocystis 6803 led to redirection of cellular energy towards faster growth under high light and simulated outdoor light conditions in photobioreactors, accompanied by higher energy charge (concentration ratio of ATP / (ATP+ADP)), and increased photosynthetic oxygen evolution capacities. Such manipulation of energy metabolism may have potential in engineering microalgal chassis cells to increase productivity of biomass or target metabolites.